(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
The literary image of Juan Moreira was maintained, throughout the history of the Argentinean Literature, thanks to a discursive genealogy that recuperated and brought new meaning to the distinctive characteristics of the hero created by Eduardo Gutiérrez, in his serial of 1879. One of the main reasons of this permanency is its evident malleability to condense representative characteristics that made of him a hero of popular mythification. In this uninterrupted net of significances, Milongas de John Moreyra, a book of poems by Homero Expósito, appears in 1968. Our purpose is to analyze the revisions by Expósito to the literary image of Moreira, seen from a double perspective: the gauchesque literature tradition and the universe of the tango lyrics.